2021
DOI: 10.1371/journal.pone.0251691
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of GeneXpert MTB/Rif proficiency testing program: A Case of the Uganda national tuberculosis reference laboratory/supranational reference laboratory

Abstract: Background Following the WHO’s endorsement of GeneXpert MTB/RIF assay for tuberculosis diagnosis in 2010, Uganda’s ministry of health introduced the assay in its laboratory network in 2012. However, assessing the quality of the result produced from this technique is one of its major implementation challenges. To bridge this gap, the National tuberculosis reference laboratory (NTRL) introduced the GeneXpert MTB/RIF proficiency testing (PT) Scheme in 2015. Methods A descriptive cross-sectional study on the Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Laboratories should participate in EQA activities to monitor the accuracy of the testing process ( International Organization for Standardization, 2013 ; Sciacovelli et al., 2018 ; Kabugo et al., 2021 ). The personnel performing nucleic acid POCT examinations should use the same testing system to assess samples for EQA, and there should be regulations prohibiting comparing EQA results with other laboratories.…”
Section: Quality Assurance Measuresmentioning
confidence: 99%
“…Laboratories should participate in EQA activities to monitor the accuracy of the testing process ( International Organization for Standardization, 2013 ; Sciacovelli et al., 2018 ; Kabugo et al., 2021 ). The personnel performing nucleic acid POCT examinations should use the same testing system to assess samples for EQA, and there should be regulations prohibiting comparing EQA results with other laboratories.…”
Section: Quality Assurance Measuresmentioning
confidence: 99%
“…One of the pioneering devices is the GeneXpert platform with the MTB/RIF assay (Cepheid Inc. Sunnyvale CA, USA), which detects M. tuberculosis as well as the mutations that confer resistance to first-line therapies [12,13]. These platforms, distributed to a network of nearly 150 laboratories, are now utilized for routine tuberculosis (TB) across Uganda [14]. However, multiple studies have shown that device implementation alone did not reduce TB-associated mortality, the proportion of people who had initiated treatment, nor the time to treatment for people with a positive test result, even though detection rates were increased [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In many lower-middle-income countries (LMIC), PT programs have been hard to set up due to costs and limitations in technical capacity. In Uganda, the national tuberculosis reference laboratory (NTRL) which is also a WHO Supra-National Reference Laboratory (Uganda-SRL) initiated the preparation of Ultra panels using a liquid matrix which was associated with the need for special storage and transportation conditions, poor stability and high rates of cross-contamination during preparation stages [8,9]. Moreover, effective PT should be conducted biannually requiring preparing of fresh panels for each round which is costly and labor-intensive [8].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the rigorous and expensive biannual preparations processes while maintaining semiannual PT rounds, the Uganda-SRL adopted the use of DTS, a method that had been used by the United States centers for disease control and prevention (CDC) and in other disease PT schemes such as HIV viral load testing [8,10,11]. We designed this study to demonstrate the stability of DTS panels and compatibility with testing protocol when stored under different environmental conditions for one year.…”
Section: Introductionmentioning
confidence: 99%